2008
DOI: 10.1103/physrevd.78.114008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperon polarization in unpolarized scattering processes

Abstract: Transverse polarization in the Hyperon (Λ) production in the unpolarized deep inelastic scattering and pp collisions is studied in the twist-three approach, considering the contribution from the quark-gluon-antiquark correlation distribution in nucleon. We further compare our results for deep inelastic scattering to a transverse momentum dependent factorization approach, and find consistency between the two approaches in the intermediate transverse momentum region. We also find that in pp collisions, there are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 46 publications
2
61
0
Order By: Relevance
“…This implies that the nonderivative terms vanish identically, which is consistent with what was found by direct calculation in [13]. This way we finally obtained the following result:…”
Section: Pos(dis2016)222supporting
confidence: 80%
See 2 more Smart Citations
“…This implies that the nonderivative terms vanish identically, which is consistent with what was found by direct calculation in [13]. This way we finally obtained the following result:…”
Section: Pos(dis2016)222supporting
confidence: 80%
“…In this contribution, a parton coming from the proton with the momentum p ′ has a momentum x ′ p ′ and a quark fragmenting into the final Λ ↑ has a momentum p c = P h /z. Twist-3 quark-gluon correlation function contributes from the proton with the momentum p. The SGP contribution was calculated in the previous studies [12,13] and it was shown that the non-derivative term vanishes [13], which is in contrast to the case of p ↑ p → πX. In this section, we develop a master formula for this contribution, which has an advantage that it can simplify the actual calculation and make clear the origin of the vanishing nonderivative term.…”
Section: Sgp Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that f ⊥ (1) 1T (x) evolves logarithmically with Q 2 just like f 1 (x), only falling off faster at a given x value as Q 2 increases. The evolution has also been calculated for moments of other TMD PDFs such as h ⊥ (1) 1 [44,48,49] and is similar to that of f ⊥(1)…”
Section: Jhep10(2011)021mentioning
confidence: 99%
“…In analogy to the T-odd quark TMDs [44][45][46], all three T-odd gluon TMDs can be perturbatively calculated in the collinear twist-3 formalism at large transverse momentum. The hard coefficients entering in these expressions are usually different for different gauge links appearing in the gluon matrix element given in Eq.…”
Section: Tmentioning
confidence: 99%